Acromioclavicular joint problems in athletes and new methods of management - Rios, C. G.; Mazzocca, A. D. (Clinics in Sports Medicine, 2008)
The acromioclavicular (AC) complex consists of bony and ligamentous structures that stabilize the upper extremity through the scapula to the axial skeleton. The AC joint pathology in the athlete is generally caused by 1 of 3 processes: trauma (fracture, AC joint separation, or dislocation); AC joint arthrosis (posttraumatic or idiopathic); or distal clavicle osteolysis. This article presents systematically the relevant anatomy, classification, evaluation, and treatment of these disorders. Management of AC joint problems is dictated by the severity and chronicity of the injury, and the patient's needs and expectations.